Misophonia in Children with Tic Disorders: A Case Series. Issue 6 (July 2018) - Robinson, Sally; Hedderly, Tammy; Conte, Giulia; Malik, Osman; Cardona, Francesco
ABSTRACT: Objective: Misophonia is a condition characterized by the dislike or hatred (miso) of specific sounds (phonia) that results in an extreme emotional response. There has been growing interest in misophonia, with emerging evidence from neurodevelopmental populations and ongoing debate regarding the psychiatric classification and the mechanisms underlying this phenomenon. This is the first article to report on misophonic experiences and associated clinical characteristics in young people with tic disorders. Method: In this article, we present the cases of 12 children and young people with tic disorders who have attended clinics in the United Kingdom and Italy who report misophonia. Misophonia was classified as a selective aversive response in accordance with the criteria proposed by Schröder. Results: These cases support the view that a range of auditory stimuli may lead to negative/aversive emotional responses of varying degrees, with misophonia seeming to contribute to behavioral reactions. Among these, the most frequent was anger outbursts, followed by an increase in tics, trigger avoidance, repetition of the sound, and self-injurious behavior. No single treatment approach was effective, with some patients responding to cognitive behavioral therapies and others to pharmacological support. Conclusion: We postulate that misophonia could be an underestimated causative phenomenon for abrupt emotional dysregulation in individuals with tic disorders and should be considered as part of a comprehensive clinical assessment. This article presents findings of relevance to general discussions regarding the classification of misophonia, as well as the potential relationship between sensory abnormalities and the broader phenotype of tic disorders during development.